A Study on the Maturity of Risk Management using the RIMS Risk Maturity Model® Approach in Investigating Activities at Law Enforcement Agencies for Corruption - Dedy Simanungkalit; Agustinus Nicholas L. Tobing (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze how to use the RIMS risk maturity model to evaluate the implementation of risk management in a law enforcement agency in Indonesia in investigating corruption and the gap between the existing implementation and the ideal conditions as suggested in the RIMS Risk Maturity Model. This descriptive qualitative research with a case study approach obtained data from external sources of the organization in the form of literature data and internal sources of the organization in direct observations, document analysis, and interviews with related parties within the organization. This research provides a tool for organizations, particularly organizations similar to the object of this research, to assess how to implement risk management processes by following general best practices. The maturity assessment results show that the risk management maturity level in the XYZ agency is in the Tier-2 position, and there is still a large gap between the current condition and the target maturity level. The XYZ agency should immediately start integrating risk management into all business processes and performance management to improve its risk management maturity level.